PENGARUH PROFITABILITAS, STRUKTUR MODAL, DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN - Annisa Zalfa Nur Alya Hardiansyah, (2023)
This research aims to examine the influence of profitability, capital structure, and managerial ownership on firm value with a firm size as a variable control. The population in this research is the mining companies listed on the Indonesia Stock Exchange (IDX) in period 2018 up to 2021. Data collected by purposive sampling method and the sampling result obtained are 100 sampels. The analysis technique used multiple linear regression analysis. The result show that profitability has a significant positive effect on firm value (first hypothesis is accepted), capital structure has a significant positive effect on firm value (second hypothesis is rejected), and managerial ownership has a significant positive effect on firm value (third hypothesis is rejected).